The Effect of Financial Distress, Audit Opinion, Management Turnover, and Profitability on Auditor Switching - Apriliani, Ribka; Nurkholis, Nurkholis (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This research aimed to provide empirical evidence regarding the effect of financial distress, audit opinion, management turnover, and profitability on auditor switching in the manufacturing sector companies listed on the Indonesian Stock Exchange (IDX). The research uses logistic regression analysis considering that the dependent variable is dichotomous. The data used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange. Data on this study were collected using purposive sampling from 39 manufacturing companies with the observation period from 2018 to 2021. The result of the study shows that financial distress and audit opinion affect auditor switching, while management turnover and profitability do not affect auditor switching.